Ageing Population: Challenge for New Quality of Social Policy; The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 26 : Responsible Research and Innovation (RRI 2016) - Barysheva G. A. Galina Anzelmovna; Nedospasova O. P. Olga Pavlovna; Malanina V. A. Veronika Anatolievna; Berkalov S. V. Sergey Vitalievich (2017, 2017)
Title screen